Genetic studies on physiological traits in wheat (Triticum aestivum L.) under normal and water stress conditions - Naroui Rad, Mohammad Reza (2013)
Drought is a worldwide problem constraining global crop production and recent global climate change has made this situation more serious for the purpose of crop production, yield improvement and yield stability under water stress conditions.The development of drought tolerant varieties is the best option to overcome this problem. Eight contrasting genotypes (four drought tolerant genotypes Irena/Babax/ /Pastor, S-78-11, Chamran and Veery/Nacozari and of drought susceptible and semi susceptible varieties). Tajan, Moghan3, Hamoon and Hirmand were crossed in half diallel matings at the Agriculture and Natural Resources Research Centre of Sistan, Iran. F1 hybrids along with their parents were grown at the Experimental Farm of the Faculty of Agriculture, Universiti Putra, Malaysia under two conditions; irrigated and water deficit. Data were recorded for some physiological parameters and were analysed to understand the genetic mechanisms of these traits. Also, this study used molecular marker approaches in order to analyse the molecular genetics of drought resistance in segregated populations to identify quantitative trait loci (QTL) conferring resistance against drought stress in the F2 population derived from a cross of cultivar S-78-11 (tolerant) line and cultivar Tajan (susceptible) by Bulked Segregant Analysis (BSA). The results of the genetic analysis and graphical analysis revealed that the over dominant action of genes for height, chlorophyll a, b, (a+b), chlorophyll content, chlorophyll fluorescence, stomatal conductance, cell membrane stability, flag leaf area, proline content, relative water content (RWC) and plant grain yield remained unchanged under irrigated and rain-fed conditions. Sometimes the graphical analysis did not match the genetics components and this contradiction in the graphic representation and the components of variance appeared to be due to residual heterozygosity in the parents. Recessive and dominant gene controlled for chlorophyll a and RWC under irrigated and stress conditions and for Veery/Nacozari gene control from the dominant gene for chlorophyll content in the first generation changed to recessive gene control under the rainsfed conditions. Under special conditions (irrigated or stress) some traits like chlorophyll a and RWC have tended to be controlled by both recessive and dominant genes. It was also found that gene activity for many characters remained unchanged in different environments. The mean squares due to GCA and SCA were highly significant for all the traits in the F1, F2 and F3 generations with an exception of SCA for the chlorophyll content in first generation and GCA for flag leaf area. The general reduction of heterosis in the F2 generation was due to a decrease in heterozygosity through allelic fixation. Generally, predicted or expected inbreeding depression was higher than that observed for all traits, except for chlorophyll fluorescence. Cultivars S-78-11 and chamran was the best combiner for the reduction of stomatal conductance and grain yield under drought stress in three generations. In irrigated conditions, cross Veery/Nacozari×Hirmand had good performance of grain yield, but, in stress conditions, the crosses Irena×chamran and S-78-11×chamran had high values for the SCA. A total of 41 SSR primer pairs were used to screen the parents; five polymorphic primer pairs were identified which showed polymorphisms between parents, and three of them strongly amplified polymorphic bands among the F2 population. The continuous distribution of the RWC in the F2 population ranged from 62% to 86%. In this study, frequency distributions were examined to detect the extent of phenotypic variations occurring with high and low RWC. The linkage relationship between the SSR markers Xgwm182, Xgwm292, and Xgwm410 and the RWC as an indicator of drought tolerant genes was estimated using an F2 population derived from S78-11 × Tajan. The segregation ratio of the tolerant and the susceptible plants for tolerance to drought fitted the expected ratio of 1:2:1, indicating a codominant inheritance of this trait.